An efficient bi-layer intumescent paint metal laminate fire barrier for various substrates: Extension to other application. Issue 1 (1st January 2021) - Geoffroy, Laura; Samyn, Fabienne; Jimenez, Maude; Bourbigot, Serge
Abstract: Different types of passive fireproofing materials exist such as intumescent paints. Our approach was to modify the design the material instead of changing the formulations. By combining two concepts namely intumescence and delamination, and adjustable design, new effective fire barrier was developed to protect composites. It was evaluated using a burn-through fire scenario (heat flux of 116 kW/m 2 and temperature of flame of 1100 °C). The fire barrier revealed to provide fire protection to the composite and stabilized the temperature at the backside of the composite plate under 200 °C. Characterisations (cross-section observations, expansion measurements, etc.) were carried out on the samples and a mechanism of action was proposed. Graphical Abstract: UF0001